2020
DOI: 10.48550/arxiv.2009.04585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stringy invariants and toric Artin stacks

Abstract: We propose a conjectural framework for computing Gorenstein measures and stringy Hodge numbers in terms of motivic integration over arcs of smooth Artin stacks, and we verify this framework in the case of fantastacks, which are certain toric Artin stacks that provide (non-separated) resolutions of singularities for toric varieties. Specifically, let X be a smooth Artin stack admitting a good moduli space π : X → X, and assume that X is a variety with log-terminal singularities, π induces an isomorphism over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the good moduli space map X → Y is a natural candidate for a nice resolution of singularities by a smooth Artin stack. In [SU20], the authors introduced a conjectural (proven in the toric case) framework that uses motivic integration for the stack X to study the stringy Hodge numbers of the singular variety Y . This framework suggested that when X → Y is birational and has exceptional locus with codimension at least 2, there should be a motivic change of variables formula making X behave like a crepant resolution of Y (see [SU20, Conjecture 1.1 and Theorem 1.7] for precise details).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the good moduli space map X → Y is a natural candidate for a nice resolution of singularities by a smooth Artin stack. In [SU20], the authors introduced a conjectural (proven in the toric case) framework that uses motivic integration for the stack X to study the stringy Hodge numbers of the singular variety Y . This framework suggested that when X → Y is birational and has exceptional locus with codimension at least 2, there should be a motivic change of variables formula making X behave like a crepant resolution of Y (see [SU20, Conjecture 1.1 and Theorem 1.7] for precise details).…”
Section: Introductionmentioning
confidence: 99%
“…We expect a better understanding of this condition will have applications to studying stringy Hodge numbers. As an example of such an application, we end this introduction by posing the following natural question, which explicitly ties Theorem 1.3 and Definition 1.6 back to the framework proposed in [SU20].…”
Section: Introductionmentioning
confidence: 99%